Sport, industry and industrial sport in Britain before 1914: review and revision. Issue 3 (15th March 2016) - Vamplew, Wray
Abstract: This article focuses on three aspects of the historical relationship between sport and industry. First, it will assess the view that modern sport was a lagged by-product of the Industrial Revolution which then was exported round the world from the first modernized economy. Second, it will consider sport as an industry in its own right examining the early commercialization associated with sport, the nature of the sports product and the often neglected issue of entrepreneurship. Finally, it will turn to workplace sport which demands attention not only due to the sheer scale of its extent but also for the apparent approach to some form of gender equality in the provision of sports facilities.